PENTINGNYA KESEJAHTERAAN PSIKOLOGIS GURU DALAM MENCIPTAKAN LINGKUNGAN BELAJAR YANG KONDUSIF - Hubbil Khair (Jurnal Ilmu Pendidikan dan Kearifan Lokal, 2025)
Teacher psychological well-being is a very important factor in creating a conducive and effective learning environment. Teachers who have good psychological well-being tend to be more innovative, creative, and able to establish positive relationships with students, thereby increasing student motivation and learning outcomes. This study discusses factors that influence teacher psychological well-being, such as social support, workload, and work-life balance. In addition, the impact of teacher well-being on teaching performance, relationships with students, and classroom management is also discussed. The research method used is a literature study with a qualitative approach. The results of the study indicate that to improve teacher well-being, strategies are needed such as strengthening social support, better workload management, and increasing awareness of mental health through training and counseling services. With the implementation of these strategies, it is hoped that teacher psychological well-being can be improved, so that it can contribute to improving the quality of education in schools